Gla-Rich protein is associated with vascular calcification, inflammation, and mineral markers in peritoneal dialysis patients - MARREIROS, CATARINA (2024)
Vascular calcification (VC) is a crucial risk factor for cardiovascular diseases (CVD), particularly in chronic kidney disease (CKD) populations. However, the specific relationship between VC and end-stage renal disease (ESRD) patients undergoing peritoneal dialysis (PD) remains to be fully understood. The identification of new biomarkers to improve VC diagnosis and monitoring would significantly impact cardiovascular risk management in these high-risk patients. Gla-rich protein (GRP) is a VC inhibitor and an anti-inflammatory agent and thus is a potential VC marker in CKD. Here we explored the potential role of GRP as a marker for CVD and investigated the impact of VC in 101 PD patients. Methods: Circulating total Gla-rich protein (tGRP) was quantified in serum and in 24 h dialysate samples. VC score (VCS) was determined using the Adragão method. Results: Serum tGRP was negatively associated with VCS, serum calcium (Ca), phosphate (P), and high-sensitivity C-reactive protein (hsCRP), while it was positively associated with magnesium (Mg). A total of 35.6% of PD patients presented with extensive calcifications (VCS ≥ 3), and the lowest tGRP serum levels were present in this group (419.4 ± 198.5 pg/mL). tGRP in the 24 h dialysate was also negatively associated with VCS and with serum Ca and P. Moreover, serum Ca, P, and VCS were identified as independent determinants of serum tGRP levels. Conclusions: The association of serum tGRP with VC, mineral, and inflammation markers reinforces its potential use as a novel VC biomarker in CKD patients undergoing PD.